Antibiofilm Effect of Rambutan Leaf Extract (Nephelium lappaceum L.) against Aggregatibacter actinomycetemcomitans and Treponema denticola (in vitro) - Salsabila, Garina; Soulissa, Abdul G.; Widyarman, Armelia S. (e-GiGi, 2022)
Abstract: Commonly, periodontal disease is caused by bacteria in subgingival plaque, such as Aggregatibacter actinomycetemcomitans and Treponema denticola. Rambutan leaf (Nephelium lappaceum L.) contains phenolic compounds that can act as antibacterial; therefore, it can be an alternative for chemical treatment of this disease. This study aimed to determine the effect of rambutan leaf extract against A. actinomycetemcomitans and T. denticola biofilm adhesion. This was an experimental and laboratory study using the post-test only control group design. The biofilm adhesion resistance test was done by using the biofilm assay method with crystal violet staining in 24 hours of incubation time. The material used was rambutan leaf extract in concentrations of 100%, 50%, 25%, 12.5%, 6.25%, and 3.125%. The optical density of biofilm was measured by using a microplate reader with a wavelength of 490 nm. Data were analyzed by using one-way ANOVA and Post-Hoc LSD (p<0.05). The results showed that rambutan leaf extract was most effective in inhibiting biofilm adhesion at 100% of concentration with an average optical density of 0.028 against A. actino-mycetemcomitans, and at 50% concentration with an average OD of 0.120 against T. denticola. In conclusion, rambutan leaf extract can inhibit biofilm adhesion of Aggregatibacter actinomycetem-comitans and Treponema denticola. Keywords: periodontal disease; rambutan leaf extract; Nephelium lappaceum L.; Aggregatibacter actinomycetemcomitans; Treponema denticola Â Abstrak: Umumnya penyakit periodontal disebabkan oleh bakteri pada plak subgingiva, seperti Aggregatibacter actinomycetemcomitans dan Treponema denticola. Alternatif untuk perawatan kimiawi penyakit ini dapat berupa obat herbal, seperti daun rambutan (Nephelium lappaceum L.). Ekstrak daun rambutan mengandung senyawa fenolik yang berkhasiat sebagai antibakteri. Penelitian ini bertujuan untuk mengetahui efek ekstrak daun rambutan terhadap perlekatan biofilm A. actinomycetemcomitans dan T. denticola. Jenis penelitian ialah eksperimental laboratoris dengan post-test only control group design. Uji hambatan perlekatan biofilm dilakukan dengan metode biofilm assay dan pewarnaan crystal violet dalam masa inkubasi 24 jam. Bahan uji ialah ekstrak daun rambutan konsentrasi 100%, 50%, 25%, 12,5%, 6,25%, dan 3,125%. Optical density biofilm kedua jenis bakteri diukur menggunakan microplate reader dengan panjang gelombang 490 nm. Data dianalisis dengan uji ANOVA satu jalan dan Post-Hoc LSD (p<0,05). Hasil penelitian menunjukkan ekstrak daun rambutan paling efektif dalam menghambat perlekatan biofilm pada konsentrasi 100% dengan rerata optical density 0,028 terhadap A. actinomycetemcomitans dan konsentrasi 50% dengan rerata OD 0,120 terhadap T. denticola. Simpulan penelitian ini ialah ekstrak daun rambutan dapat menghambat perlekatan biofilm Aggregatibacter actinomycetemcomitans dan Treponema denticola. Kata kunci: penyakit periodontal; ekstrak daun rambutan; Nephelium lappaceum L.; Aggregatibacter actinomycetemcomitans; Treponema denticola